Association of interleukin-6, ferritin, and lactate dehydrogenase with venous thromboembolism in COVID-19: a systematic review and meta-analysis - Haiyu Liu; Ningjing Guo; Qixian Zheng; Qianyuan Zhang; Jinghan Chen; Yuanyuan Cai; Qiong Luo; Qian Xu; Xiangqi Chen; Sheng Yang; Suyun Zhang (BMC Infectious Diseases, 2024)
Abstract Background Coronavirus disease 2019 (COVID-19) is frequntly accompanied by venous thromboembolism (VTE), and its mechanism may be related to the abnormal inflammation and immune status of COVID-19 patients. It has been proved that interleukin-6 (IL-6), ferritin and lactate dehydrogenase (LDH) may play an important role in the occurrence of VTE in COVID-19 infection. But whether they can server as predictors for VTE in COVID-19 is still unclear. In this study, we performed a systematic review and meta-analysis to compare IL-6, ferritin and LDH in VTE and non-VTE COVID-19 patients in order to shed light on the prevention and treatment of VTE. Methods Related literatures were searched in PubMed, Embase, Web of Science, Google Scholar, China National Knowledge Infrastructure (CNKI), WANGFANG. COVID-19 patients were divided into VTE group and non-VTE group. Meta-analysis was then conducted to compare levels of IL-6, ferritin and LDH between the two groups. Results We finally included and analyzed 17 literatures from January 2019 to October 2022. There was a total of 7,035 COVID-19 patients, with a weighted mean age of 60.01 years. Males accounted for 62.64% and 61.34% patients were in intensive care unit (ICU). Weighted mean difference (WMD) of IL-6, ferritin and LDH was 31.15 (95% CI: 9.82, 52.49), 257.02 (95% CI: 51.70, 462.33) and 41.79 (95% CI: -19.38, 102.96), respectively. The above results indicated that than compared with non-VTE group, VTE group had significantly higher levels of IL-6 and ferritin but similar LDH. Conclusion This systematic review and meta-analysis pointed out that elevated levels of IL-6 and ferritin were significantly possitive associated with VTE, thus could be used as biological predictive indicators of VTE among COVID-19 patients. However, no association was found between level of LDH and VTE. Therefore, close monitoring of changes in IL-6 and ferritin concentrations is of great value in assisting clinicans to rapidly identify thrombotic complications among COVID-19 patients, hence facilitating the timely effective managment. Further studies are required in terms of the clinical role of cytokines in the occurrence of VTE among COVID-19 infection, with more reliable systematic controls and interventional trials.